(untitled) (Research, Society and Development, 2022)
The emphasis of the study presented here is business management focused on finance, where it presents related contents in question, based on the curriculum presented by the MBA course in Finance and Controllership. In addition to the relevant knowledge acquired through a research of the theme, a bibliographical research was carried out and complemented with the opinions presented throughout the study, through a dissertation-expositive text, considering authors such (Cavalcanti, Dewey, Hora, Longenecker, Luck e, Rodrigues), among others of equal relevance. The study presented is considered of great importance, because the knowledge acquired will help the author of the article and the reader to accelerate and optimize the performance in the business, with emphasis on the financial part of them, essential skills for the realization of an assertive diagnosis and for decision making, a routine point for the professional. Through a contextualization and bibliographic research, the work seeks to present the management of different businesses and the environment in which they are inserted in Brazil, according to the manual presented and the required standards.